Determinants of Achievement in Scientific Work: Exploring the Relationship of Leadership Style, Adversity Quotient, and Motivation - Mustafidah, Roufi'ul; Fadly, Wirawan; Rochmah, Elfi Yuliani (JURNAL AL-TANZIM, 2024)
Writing scientific work is a requirement for students. However, students still need help writing scientific papers. This study aimed to determine the effect of leadership style, adversity quotient, and motivation on scientific work achievement in Tadris IPA IAIN Ponorogo students. The approach used in this study is a quantitative approach to causal research. The data was collected using a questionnaire and analyzed using regression analysis and SEM PLS. Overall, the study results show that leadership style, adversity quotient, and motivation positively influence scientific work achievement. PLS-SEM analysis shows that the variable that has the highest contribution is the adversity quotient. Then, the indicator with the highest contribution is the ownership indicator, while the indicator that contributes the least is creative innovation, with my statement using failure as a learning tool. This research proves that leadership style, adversity quotient, and motivation influence the scientific work achievement of Tadris IPA IAIN Ponorogo students. Therefore, in improving achievement in the field of scientific work, contributions from leaders, persistence from students, and encouragement to achievement are needed.